Prenatal treatment with metronidazole induces cerebellar folia alteration in guinea pig fetuses - Čapo, Ivan Đ.; Milenković, Ivan J.; Čapo, Nataša P.; Stilinović, Nebojša P.; Vukmirović, Saša N.; Teofilović, Branislava D.; Petković, Branka B.; Sekulić, Slobodan R. (Archives of Biological Sciences, 2020)
Paper description: The neurotoxic side effect of metronidazole in therapy of adults is established but there is insufficient data about the prenatal consequences of metronidazole treatment. Pathohistological techniques were used to study the effect of metronidazole on guinea pig fetuses. Metronidazole caused cell depletion in proliferative zones of the cerebellum and decrease of the areal fraction value in all cortical layers, as well as intensive folia alteration. The presented results question the use of metronidazole during pregnancy. Abstract: The most sensitive period in brain development is during prenatal life. The use of antibiotics in pregnancy is still controversial. Recent studies revealed the high neurotoxic potential of the antibiotic and antiprotozoal medication, metronidazole. However, there are insufficient data from animal studies about prenatal treatment effects. We investigated the effect of prenatal treatment with metronidazole on cerebellar development in guinea pigs. Treatment with metronidazole was performed from the 42nd to the 49th day of gestation. On the 50th day of pregnancy, all dams were killed, and the cerebella of the fetuses were analyzed. Gross cerebellar changes characterized by malposition of the folia with partial atrophy were found in 12 of 19 fetuses in the experimental group, but in none of 20 control fetuses that received saline. The most affected were folia VII with depletion of the areal fraction of the external granular layer, molecular layer and the internal granular layer. Purkinje cells displayed cell distortion with loss of normal dendritic polarity. The investigation revealed cell depletion, with a disturbance of the cytoarchitectonic of the cerebellar cortex and folia alteration.